Curcumin inhibits WT1 gene expression in human leukemic K562 cells - Songyot Anuchapreeda (2018)
Aim: Wilms' tumor1 (WT1) gene is highly expressed in leukemic blast cells of myeloid and lymphoid origin. Thus, WT1 mRNA and protein serve as promising tumor markers for the detection of leukemia and monitoring of disease progression. The purpose of this study was to investigate the modulating effects of curcumin on WT1 gene expression in the human leukemic cell line K562. Methods: The cytotoxicity of curcumin on the K562 cell line was evaluated by using 3-(4,5-dimethyl-2 thiazoyl)-2,5-diphenyl-tetrazolium bromide (MTT) assay. The K562 cell line was treated with a non-cytotoxic dose of curcumin (5,10, or 15 μmol/L) for 13 d. The expression levels of WT1 protein and WT1 mRNA were assessed by Western blot analysis and reverse transcription-polymerase chain reaction (RT-PCR), respectively. Results: Curcumin had a cytotoxic effect on K562 leukemic cells with an inhibitory concentration at 50% (IC50) of approximately 20 μg/mL (54.3 μmol/L). Non-cytotoxic doses of curcumin, at concentrations of 5,10, and 15 μmol/L for 2 d, decreased the level of WT1 protein and WT1 mRNA in the K562 cell line in a dose-dependent manner. Similarly, curcumin at a concentration of 10 μmol/L significantly decreased the level of WT1 protein and mRNA in a time-dependent manner. Conclusion: The inhibitory effects of curcumin are associated with a decrease in the levels of both WT1 protein and WT1 mRNA. The current study provides a molecular basis for future clinical trials in leukemic patients. Thus, curcumin could be a promising chemotherapeutic agent for human leukemia. ©2006 CPS and SIMM.